Anion‐regulated binding selectivity of Cr(III) in collagen. Issue 11 (2nd November 2020) - Zhang, Yi; Mehta, Megha; Mansel, Bradley W.; Ng, Hon Wei; Liu, Yang; Holmes, Geoff; Le Ru, Eric C.; Prabakar, Sujay
Abstract: We present a mechanism for the selectivity of covalent/electrostatic binding of the Cr(III) ion to collagen, mediated by the kosmotropicity of the anions. Although a change in the long‐range ordered structure of collagen is observed after covalent binding (Cr(III)‐OOC) in the presence of SO4 2− at pH 4.5, the νsym (COO − ) band remains intense, suggesting a relatively lower propensity for the Cr(III) to bind covalently instead of electrostatically through Cr(H2 O)6 3+ . Replacing SO4 2− with Cl − reduces the kosmotropic effect which further favors the electrostatic binding of Cr(III) to collagen. Our findings allow a greater understanding of mechanism‐specific metal binding in the collagen molecule. We also report for the first time, surface‐enhanced Raman spectroscopy to analyze binding mechanisms in collagen, suggesting a novel way to study chemical modifications in collagen‐based biomaterials. Abstract :